Stock Returns over the FOMC Cycle - CIESLAK, ANNA; MORSE, ADAIR; VISSING‐JORGENSEN, ANNETTE (Journal of Finance, 2019)
ABSTRACT We document that since 1994, the equity premium is earned entirely in weeks 0, 2, 4, and 6 in Federal Open Market Committee (FOMC) cycle time, that is, even weeks starting from the last FOMC meeting. We causally tie this fact to the Fed by studying intermeeting target changes, Fed funds futures, and internal Board of Governors meetings. The Fed has affected the stock market via unexpectedly accommodating policy, leading to large reductions in the equity premium. Evidence suggests systematic informal communication of Fed officials with the media and financial sector as a channel through which news about monetary policy has reached the market.